PROFESSIONAL AND PEDAGOGICAL TRAINING OF FUTURE TECHNOLOGY AND LABOR EDUCATION TEACHERS - Raxmatulla Sadikovich Shermuxamedov (Bright Mind Publishing, 2025)
This article explores the professional and pedagogical training of future teachers specializing in technology and labor education within the context of higher pedagogical institutions in Uzbekistan. It emphasizes the importance of integrating theoretical knowledge with practical competencies to prepare future educators capable of addressing contemporary educational and technological challenges. The study analyzes the current state of teacher training programs, highlights gaps between curriculum content and labor market requirements, and suggests innovative strategies for enhancing professional preparedness. By examining national standards, pedagogical frameworks, and international best practices, the article provides a comprehensive perspective on the development of professional and pedagogical competencies among students pursuing careers in technology and labor education.
Keywords: Professional training, pedagogical competencies, teacher education, labor education, technology teaching, vocational skills, higher pedagogical education, curriculum development, educational innovation.